USM-UNIVERSITY OF GLASGOW VENTURING INTO ACADEMIC COOPERATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 15 September 2016 – Universiti Sains Malaysia (USM) and University of Glasgow (UoG) Scotland today signed a Memorandum of Understanding (MoU) on having academic cooperation within the next three years.